DAMPAK PEMBINAAN REFLEKTIF TERHADAP PENGEMBANGAN PROFESIONALISME DAN KETERAMPILAN MENGAJAR GURU - Daman Rasman Syarif Hidayat (Globalwriting Academica Consulting & Publishing, 2020)
Reflective coaching as a formative model mainly aims to evaluate and help teachers develop teaching skills. To understand the context of reflective coaching, one needs to understand the meaning of reflection. The method used in this study is a qualitative method with a pre-experimental approach. This research was conducted during the first semester of the 2018-2019 Academic Year. 30 teachers from Al-Ihsan High School Jakarta were joined. It consists of 16 female teachers and 14 male teachers with ages ranging from 22 to 40 years. The study was conducted during the teacher education program training. From this research, it can be seen that reflective coaching, in this context, is considered to play an important role in creating efforts that prioritize collaboration. It is also a viable and potentially reusable monitoring model in both pre-service and in-service contexts.